Shortages of medicines in a psychiatric hospital in Cyprus - Petrou P.; Sophie Ioannou S. (Sciendo, 2022)
The incidence of drug shortages has surged in recent years and it poses a major threat to public health worldwide. It can also downgrade the quality of care provided to patients. Data concerning shortages pertinent to mental health care are scarce, while treatment continuity is vital to avert disease recurrence and deterioration of patients' mental health.